ANALISIS HAMBATAN MEMBACA PERMULAAN SISWA KELAS 1 DI SDN SUNGAI ANDAI 4 BANJARMASIN - Rufina; Rusdiana, Ida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Beginning reading is a fundamental skill that first-grade elementary school students must master as the foundation for participating effectively in the learning process. However, some students still experience reading difficulties, such as recognizing letters, distinguishing between similar-looking letters, and reading simple words and sentences. This study aims to describe students' beginning reading skills, identify the reading difficulties they experience, and analyze the factors contributing to these difficulties among first-grade students at SDN Sungai Andai 4 Banjarmasin. This study employed a qualitative approach with a narrative research design. The research subjects consisted of first-grade students who experienced reading difficulties and the classroom teacher as a supporting informant. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The validity of the data was ensured through triangulation. The findings revealed that the beginning reading skills of some students were still at the initial stage, as indicated by limited letter recognition, reading by spelling out words, and a lack of fluency in reading simple words and sentences. The identified reading difficulties included recognizing and distinguishing letters, reading fluently, and comprehending reading texts. These difficulties were influenced by internal factors, such as low learning interest and motivation, and external factors, including limited family support and a lack of reading habits at home. Therefore, appropriate instructional strategies tailored to students' needs are required to improve their beginning reading skills.